(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
In terms of the prokaryotic expression system Escherichia coli, it is well-known that incubation temperature, OD_600 value, isopropyl thiogalactoside concentration and time of induction are general factors which can directly affect the final protein's expression. The traditional method for this optimization is to study these factors which may influence the protein expression separately, thus, the interactions between factors are ignored. Design of experiment is a time-saving and cost-effective methodology for increasing the productivity and improving the quality of a product. In order to verify if design of experiment is suitable for the optimization of a protein expression and also to reveal if there is any interaction between the factors that have a significant influence on the protein's expression, the optimization of expression for the protein Bmlebocin3 was carried out using the design of experiment concept. Bmlebocin3 is an antimicrobial peptide in the silkworm, Bombyx mori. It has a unique precursor form which was suitable for this investigation. In this study, the Bmlebocin3 gene was cloned and expressed in Escherichia coli, and then this expression was optimized by design of experiment. The results revealed that through the use of design of experiment, in addition to quantifying the separate effects of the OD_600 value and the time of induction, it demonstrated that, their interaction can significantly affect the expression of Bmlebocin3. Furthermore, the best condition for the Bmlebocin3 's expression was identified through fewer experiments. This proved that design of experiment can be used as an efficient way to optimize the protein expression.